Cardioprotective effect of novel inhibitors of G-Protein-Coupled Receptor Kinase 2 (GRK2) - Echeverría, Emiliana Beatriz (2023)
GRK2 activity has been validated as a promising target for cardiovascular diseases, the major global causes of death. Via virtual screening and cell-based assays,we identified commercial molecules that inhibit GRK2'sRGS homology domain (RH). Based on that, we developed novel analogs, L96B and L94C, that were synthesized and tested as GRK2 inhibitors. This study aimed to preclinically characterize their mechanism of action and potential therapeutic efficacy.